Survey of genitourinary medicine specialist registrars in the United Kingdom regarding genital dermatology training. (July 2016) - Hartley, A; Bates, CM; Sashidharan, PN
The British Association for Sexual Health and HIV Genital Dermatology Special Interest Group (SIG) conducted a survey of specialist registrar training in genital dermatology (GD) to inform future training provision provided by the group and other services. The survey shows that training in GD is variable with most trainees receiving GD training through formal lectures or ad hoc clinical teaching, with fewer trainees having access to specialist GD clinics. There is mixed confidence in diagnosis and use of topical steroids, and few trainees are independent in GD practical procedures. Many trainees feel training could be improved with requests for a formalised attachment, formal qualification and greater training in practical procedures. The GD SIG, in liaison with British Association for Sexual Health and HIV (BASHH), aims to optimise GD training for registrars. Plans for improved resources are in progress, including a practical skills course and e-learning. It is hoped this survey will also inform GD training at both local and national levels.